The Modulation of Regulatory T Cells via HMGB1/PTEN/β-Catenin Axis in LPS Induced Acute Lung Injury - Zhou, Min; Fang, Haoshu; Du, Min; Li, Changyong; Tang, Rui; Liu, Haiyan; Gao, Zhi; Ji, Zongshu; Ke, Bibo; Chen, Xu-Lin (Frontiers in Immunology, 2019)
Sepsis-induced acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) remains the leading complication for mortality caused by bacterial infection. The regulatory T (Treg) cells appear to be an important modulator in resolving lung injury. Despite the extensive studies, little is known about the role of macrophage HMGB1/PTEN/β-catenin signaling in Treg development during ALI. Objectives: This study was designed to determine the roles and molecular mechanisms of HMGB1/PTEN/β-catenin signaling in mediating CD4+CD25+Foxp3+ Treg development in sepsis-induced lung injury in mice. Setting: University laboratory research of First Affiliated Hospital of Anhui Medical University. Subjects: PTEN/-catenin Loxp and myeloid-specific knockout mice. Interventions: Groups of PTENloxp/-cateninloxp and myeloid-specific PTEN/-catenin knockout (PTENM-KO/-cateninM-KO) mice were treated with LPS or recombinant HMGB1 (rHMGB1) to induce acute lung injury. The effects of HMGB1-PTEN axis were further analyzed by in vitro co-cultures. Measures and Main Results: In a mouse model of ALI, blocking HMGB1 or myeloid-specific PTEN knockout (PTENM-KO) increased animal survival/body weight, reduced lung damage, increased TGF-β production, inhibited the expression of RORt and IL-17, while promoting β-catenin signaling and increasing CD4+CD25+Foxp3+ Tregs in LPS- or rHMGB-induced lung injury. Notably, myeloid-specific β-catenin ablation (β-cateninM-KO) resulted in reduced animal survival and increased lung injury, accompanied by reduced CD4+CD25+Foxp3+ Tregs in rHMGB-induced ALI. Furthermore, disruption of macrophage HMGB1/PTEN or activation of β-catenin significantly increases CD4+CD25+Foxp3+ Tregs in vitro. Conclusions: HMGB1/PTEN/β-catenin signaling is a novel pathway that regulates Treg development and provides a potential therapeutic target in sepsis-induced lung injury.